WAYS OF REPRESENTING THE PHONETIC LEVEL OF CHILDREN’S SPEECH IN FICTION (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-4-48-58Abstract. The article focuses on the analysis of two English coming-of-age novels “Room” by E. Donoghue and “The Night Rainbow” by C. King, written from the point of view of pre-school children. This type of narration lets us trace features of children’s speech and identify language markers used for their depiction. Onomatopoeia is the most frequently used device that represents the phonetic level of a child-narrator’s speech. The writers apply it both on their own and in combination with other phonetic stylistic devices: reduplication and alliteration. The authors also analyse graphical stylistic devices, namely capitalization and italics for highlighting onomatopoeic units in the text. In some cases, the writers aim to convey physical characteristics of sounds such as their length and volume. The effect is achieved with the help of the English alphabet. The depiction of the pronunciation features of individual words (contortion of sounds, their exchange, contraction of clusters, etc.) occurs rarely. This might relate to the difficulty of depicting these peculiarities in writing. Such a choice of devices helps demonstrate pre-school children’s interest in the acoustic aspect of the world around them and represents their desire to imitate the sounds that they hear.Key words: “Room” by E. Donoghue, “The Night Rainbow” by C. King, child-narrator, children’s speech, phonetic level of speech, onomatopoeia